Konsep Reliabilitas dalam Penelitian dan Teknik Pengujianya - Nur Saidah; Nur Mawaddah; Nur Hidayah; Zulpan Zulpan; Ahmad Husein; Arianto Arianto (Indo Publishing, 2026)
Reliability is an important part of research because it shows the extent to which an instrument is able to provide consistent results when used repeatedly. A reliable instrument is considered trustworthy and truly describes the true condition of the object being studied. Without good reliability, research data becomes difficult to account for because the results are unstable. This study uses a literature study method by examining theories and results of previous research on the concept of reliability, types of reliability, and testing techniques. The results of the study show that reliability is closely related to the stability and accuracy of a measuring instrument. Various methods such as test-retest, split-half, equivalent form, and Cronbach's Alpha can be used according to research needs. Other factors such as the number of questions, the variety of participants, and the level of difficulty also affect the size of the reliability value. By understanding the concept of reliability thoroughly, researchers can construct more consistent and reliable instruments.